Modelling the relationship between “Internet of Things”, value co-creation and innovation performance in healthcare - AL JBOUR, RADWAN SALEH (2020)
This research aims to explore the influence of “Internet of Things” (IoT) capabilities on the value co-creation and the service innovation performance of healthcare organisations. ‘Internet of Things’ is a new phenomenon, and the impact of its capabilities on service innovation performance has not been examined in a similar healthcare domain. Therefore, this study investigates the IoT capabilities from a marketing perspective of value co-creation to draw out vital elements to constitute resource integration practices and co-creation towards obtaining service innovation outcomes and achieving a competitive advantage. Also, the study attempts to theoretically contribute to the value co-creation and IoT literature by affording an empirical establishment for IoT- enabled value co-creation and demonstrating how it underpins the interaction between actors within the healthcare ecosystem. The study employed resource-based view (RBV) theory and service-dominant logic framework to develop a theoretical connection and empirically examine the influence of IoT capabilities on service innovation performance through the mediating effect of value co-creation practices. It also used the Orlikowski structuration model of technology to depict the relationship between technology and value co-creation. The study adopted the deductive, quantitative method following the positivism philosophical assumption. This method involved a survey questionnaire completed by healthcare givers (e.g. doctors, nurses, therapists) in Jordan’s private and public sectors hospitals. A pilot study was conducted to ensure the validity of the research design. It included a small-scale distribution of the survey questionnaire and interviews with individuals from the target population. Data were collected (n=208) using a drop-off pick-up method and analysed using multiple techniques, including exploratory factor analysis, confirmatory factor analysis and structural equation modelling (SEM). The study’s findings confirm the influence of IoT monitoring and collaboration capabilities on the service innovation performance and support the proposition of IoT monitoring, optimisation and collaboration impact on value co-creation practices. However, IoT control capability shows no support to innovation performance. Findings also show that monitoring is an essential capability of IoT in healthcare, suggesting that successful value co-creation heavily depends on how hospitals access, observe, contact, interact and apply their technological knowledge processes.